1995
DOI: 10.1055/s-2007-1022795
|View full text |Cite
|
Sign up to set email alerts
|

Korrelation des Cotininspiegels in Fruchtwasser, Nabelarterienblut und mütterlichem Blut

Abstract: The aim of the present study was to determine the correlation of cotinine levels in amniotic fluid and in fetal and corresponding maternal blood samples. Amniotic fluid samples (N = 130) were taken during second trimester amniocentesis, umbilical artery blood samples (N = 75) at birth, both together with corresponding maternal blood samples. Self-reported smokers showed maternal serum cotinine levels > 15 ng/ml in 93%, self-reported nonsmokers levels < 15 ng/ml in 89%. Correlation of corresponding values for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…Our findings described here extend from prior reports that concentrations of nicotine metabolites in amniotic fluid exceed those found in the corresponding maternal serum (Ruhle, Graf von Ballestrem, Pult, & Gnirs, 1995). Specifically, we demonstrate that the metabolic consequences of exposure are also compounded in the fetal compartment.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings described here extend from prior reports that concentrations of nicotine metabolites in amniotic fluid exceed those found in the corresponding maternal serum (Ruhle, Graf von Ballestrem, Pult, & Gnirs, 1995). Specifically, we demonstrate that the metabolic consequences of exposure are also compounded in the fetal compartment.…”
Section: Discussionsupporting
confidence: 89%
“…In other studies too, even though carried out during the second trimester, concentrations of cotinine in amniotic fluid were observed to be significantly lower than in maternal urine 20 and of a magnitude comparable to that seen in maternal serum. 8,20,21 Hence, we could not confirm the results of Jordanov et al 19 who found cotinine concentrations in amniotic fluid at birth that were twice as high as in maternal urine. The analyzes, however, were carried out by means of a non-specific colorimetric method, without separation between nicotine, cotinine and further metabolites.…”
Section: Discussioncontrasting
confidence: 66%
“…Cotinine concentrations measured in amniotic fluid in the second trimester, however, were much lower than those in maternal urine 20 and only slightly higher than in maternal serum. 8,20,21 It was the aim of the present study to investigate if amniotic fluid at birth is suitable for discriminating between smoking, environmental tobacco smoke (ETS) exposure and non-exposure during pregnancy when a simultaneous determination of nicotine, cotinine and trans-3 0 -hydroxycotinine (OH-cotinine) is performed by means of high-performance liquid chromatography (HPLC). 9 Furthermore, it was of great interest to compare concentrations of nicotine and its metabolites in amniotic fluid with those in maternal urine, in neonatal urine and in meconium.…”
Section: Introductionmentioning
confidence: 99%
“…Other workers too found a strong linear association between cotinine concentration in different body fluids of smoking mothers and their foetuses or neonates. [20][21][22] By contrast, in case of ETS exposure -as distinct from active smoking -a log-normal distribution is seen as the best model 23 and this has also been confirmed by own studies conducted in ETS-exposed children (unpublished observation). 17 When considering the samples of meconium passed by a newborn in succession, the total sum of nicotine and its metabolites (Sum tot ) in meconium remained constant.…”
Section: Discussionmentioning
confidence: 60%